THE POLITICAL ECONOMY OF ISLAM: ANALYZING THE INTERSECTION OF POLITICS, ECONOMICS, AND FAITH IN MUSLIM SOCIETIES - Luis Santos; Josefa Flores; Ali Khan (Yayasan Adra Karima Hubbi, 2026)
The interaction between politics, economics, and faith continues to shape institutional development, governance practices, and socioeconomic outcomes across Muslim societies. Islamic principles influence public policy, economic behavior, social welfare systems, and perceptions of political legitimacy, This study aims to analyze the intersection of political institutions, economic structures, and Islamic values in contemporary Muslim societies and to examine how these dimensions collectively influence governance effectiveness and social development. A mixed-methods comparative research design was employed, integrating quantitative indicators of governance, economic performance, Islamic finance penetration, and institutional trust with qualitative analysis of policy frameworks, religious institutions, and development practices across selected Muslim-majority countries. Findings reveal that governance effectiveness plays a central role in mediating the relationship between faith-based institutions and socioeconomic outcomes. Results further indicate that religious values contribute positively to development when supported by accountable political and economic institutions. The study concludes that the political economy of Islam is best understood as a dynamic interaction among governance structures, economic systems, and faith-based values, where institutional capacity.